Risk, Resilience, and Sustainability: How Governance in Zimbabwe Countervails this Nexus - Shumba, Dorcas (Consilience, 2017)
This paper supports the view that there is a strong correlation between risk, resilience, and sustainability and that governance has a bearing on the outcome of each of these concepts. This is to suggest that, when the nexus is unstable, there is a greater chance that poor governance will be at play and vice versa. To demonstrate this premise using evidence from Zimbabwe, the paper embarks on a socio-historical analysis of the style of governance taken by the country from its independence in 1980 till the present day, highlighting how this may have played a major role towards heightening situations of risk, decreasing the resilience of the people, subsequently stalling sustainability. The ideas conveyed in this paper will help strengthen the vision for good governance that was set by the UN as part of the post 2015 development agenda.